MAJOR SYMBOLIST POETS AND THEIR WORLD MODELS (BASED ON THE WORKS OF A. A. BLOK, V.YA. BRYUSOV, AND V.I. IVANOV) - Turgunov U. B. (Web of Journals Publishing, 2025)
The article analyzes world-building strategies in the poetics of major Russian Symbolist poets: Alexander Blok, Valery Bryusov, and Vyacheslav Ivanov. It examines the aesthetic, philosophical, and mythopoetic foundations of their creative systems that define the structure of their artistic worlds. The study reveals how each poet constructs a unique poetic universe using various symbolic and mythological paradigms. Special attention is given to the function of the symbol as a means of modeling sacred reality and engaging with archetypal collective consciousness.
Keywords: Symbolism, world-building, poetics, mythopoetics, Blok, Bryusov, Ivanov, symbol, myth, sacred.